Skip to main content
Solve for Y
Tick mark Image

Similar Problems from Web Search

Share

s\left(s+1\right)\left(s+2\right)Ys=x_{s}
Multiply both sides of the equation by sx_{s}\left(s+1\right)\left(s+2\right), the least common multiple of x_{s},s\left(s+1\right)\left(s+2\right).
\left(s^{2}+s\right)\left(s+2\right)Ys=x_{s}
Use the distributive property to multiply s by s+1.
\left(s^{3}+3s^{2}+2s\right)Ys=x_{s}
Use the distributive property to multiply s^{2}+s by s+2 and combine like terms.
\left(s^{3}Y+3s^{2}Y+2sY\right)s=x_{s}
Use the distributive property to multiply s^{3}+3s^{2}+2s by Y.
Ys^{4}+3Ys^{3}+2Ys^{2}=x_{s}
Use the distributive property to multiply s^{3}Y+3s^{2}Y+2sY by s.
\left(s^{4}+3s^{3}+2s^{2}\right)Y=x_{s}
Combine all terms containing Y.
\frac{\left(s^{4}+3s^{3}+2s^{2}\right)Y}{s^{4}+3s^{3}+2s^{2}}=\frac{x_{s}}{s^{4}+3s^{3}+2s^{2}}
Divide both sides by s^{4}+3s^{3}+2s^{2}.
Y=\frac{x_{s}}{s^{4}+3s^{3}+2s^{2}}
Dividing by s^{4}+3s^{3}+2s^{2} undoes the multiplication by s^{4}+3s^{3}+2s^{2}.
Y=\frac{x_{s}}{\left(s+1\right)\left(s+2\right)s^{2}}
Divide x_{s} by s^{4}+3s^{3}+2s^{2}.